THE FACTORS INFLUENCING GROUP LIFE INSURANCE AND COMPANY WELFARE (COMPANY CREDIT) DECISIONS ON PRIVATE HOSPITAL SERVICES IN CHACHOENGSAO - Noksiri, Trerapong; Rahothan, Jiraporn (Journal of Graduate School of Commerce-Burapha Review, 2022)
This research aimed to study the effects of individual variables on Group Life Insurance and Company Welfare decisions on Private Hospital Services in Chachoengsao. Moreover, the corporate image factors influence the private hospital services in Chachoengsao. The subjects were the population of Chachoengsao. The study’s instrument consisted of questionnaires, which were used to collect data. Statistics used for data analysis consisted of mean, percentage, standard deviation, t-test, one-way ANOVA, and Multiple Linear Regression. The results of this study indicate that the differences of individual factors—on Group Life Insurance and Company Welfare decisions on Private Hospital Services in Chachoengsao—were statistically insignificant and they were virtually all individual decisions to use Private Hospital Services. Furthermore, the corporate image factors affecting private hospital services in Chachoengsao significantly used reputation to maintain the client confidence. Corporate communication, marketing factors, medical services with advanced technology, and price factors all of these were affecting toward the decisions on private hospital services in Chachoengsao indeed.